On the extension of semi-Lipschitz functions on asymmetric normed spaces - Mustăţa, Costică (Rev. Anal. Numér. Théor. Approx., 2005)
Extension theorems for semi-Lipschitz functions and some properties of these extensions useful in approximation problems are presented. As illustration, a such problem is considered.